Radical Reclamations: Reviving Jewish Birth Practices - Handlarski, Denise (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
This article uses autoethnography to explore a rabbi’s difficult labour and birth experience and how it led her to research on Jewish birth practices. Religious and ethnic birth practices are often elided in patriarchal and Western culture, and the uncovering and reclaiming of such practices are an important site of empowerment for mothers and for women1 whose knowledges have been supressed. Through reclaiming birth practices, there is also a reclamation of traditional knowledge, bodily autonomy, women’s community, and personal empowerment. In using autoethnography, the author locates herself in the discursive formations of such reclamation and empowerment as well as engages in the Jewish cultural practice of dialogue with text and tradition, thus merging personal, professional, traditional, and transformative research, writing, and practice.